Contrast-Enhanced Ultrasonography for Screening and Diagnosis of Hepatocellular Carcinoma: A Case Series and Review of the Literature - Kathryn L. McGillen; Syeda Zaidi; Amer Ahmed; Shantell Harter; Nelson S. Yee (Medicines, 2020)
Background: Contrast-enhanced ultrasound (CEUS) is a safe and noninvasive imaging technique that can characterize and evaluate liver lesions, and has been approved for this use in the Unites States since 2016. CEUS has been shown to be similar in accuracy to computed tomography (CT) and magnetic resonance imaging (MRI) for noninvasive diagnosis of hepatocellular carcinoma (HCC) and offers several advantages in certain patient populations who have contraindications for CT or MRI. However, CEUS has inherent limitations and has not been widely employed for evaluation of HCC. Methods: We present three retrospective cases of liver lesions in patients with cirrhosis, who underwent screening for HCC using concurrent, well-timed CT and CEUS. Results: In these cases, the liver lesions were better visualized and then diagnosed as malignancy via CEUS, whereas the lesions were best appreciated on CT only in retrospect. Conclusions: In some cirrhotic patients, a focal lesion may be more easily identifiable via CEUS than on CT and thus accurately characterized, suggesting an important and complementary role of CEUS with CT or MRI. Further studies are indicated to support the use of CEUS for the diagnosis and characterization of liver lesions in screening patients at risk for developing HCC.